ALTERATION OF SULFIDE ORES OF THE SAMOLAZOVSKOE DEPOSIT, ALDAN SHIELD, IN AN EXPERIMENTAL BIOLEACHING HEAP - E.V. Belogub; K.A. Novoselov; I.B. Fadina; M.A. Rassomakhin (Минералогия)
The paper presents the results of a mineralogical study of sulfide ores of the Samolazovskoe deposit (Aldan Shield) and the products of their experimental bacterial oxidation in a heap. Pyrite and marcasite are the major minerals of primary ores. They form fine-grained crystalline and micrometer-grained to cryptocrystalline aggregates. Sphalerite, galena, chalcopyrite, pyrrhotite, fahlore, luzonite, bournonite and other Sb sulfosalts, stibnite and arsenopyrite are minor minerals. Tiemannite, coloradoite, calaverite, hessite, petzite and native gold are rare. The ores in the experimental biooxidation heap are mostly altered in its upper part. The secondary alteration products of ores include fine-grained Mg- and S-bearing calcite, smectites after feldspars, and films of Fe3+oxyhydroxides on the surface and in fractures of ore. In the lower part of the heap, technogenic processes are weak and are mainly related to the formation of gypsum. The sulfides are preserved throughout the heap vertical profile including very fine crystalline, colloform and botryoidal aggregates with a nonstoichiometric cation/anion ratio and the presence of As, Ni and Cu. The botryoidal aggregates of Fe disulfides contain galena, which forms a «microseptary» structure, which was not found in primary ores. The high-fineness native gold was found in assemblage with coloradoite and calaverite as inclusions in fine-grained aggregates of Fe disulfides. It is concluded on an insufficient impact of the bioleaching of refractory ores in an applied irrigation regime and the formation of secondary minerals that prevent the extraction of gold.